Towards a theory of quality nursing care for patients with cancer through hermeneutic phenomenology - Charalambous, Andreas; Papadopoulos, (I)Rena R.; Beadsmoore, Alan (My University, 2009)
Aim This paper is a report of a study to describe the attributes of quality nursing narrated by a sample of patients with cancer, their advocates and their nurses. Background Quality nursing care is a multifaceted concept which is open to interpretation. Studies show that while nurses are striving to succeed in providing quality care for their patients and the patients are urging for better nursing care, the complexity in understanding the concept often causes confusion among patients and nurses. Method The study was a phenomenological hermeneutical study based on the ideas of the French Philosopher Paul Ricoeur. Twenty-five patients with cancer, six advocates and twenty cancer nurses were recruited in Cyprus by a purposive method. The informants were encouraged to narrate their lived experiences of receiving and providing quality nursing care. A discussion follows whether the findings can be regarded as a theory of quality in cancer care. Findings Based on the informants' narratives the following six attributes of quality nursing care materialized: a) being valued, b) being respected c) being cared for by communicative and supportive nurses, d) being confirmed, e) being cared for religiously and spiritually and f) belonging. Conclusion The six attributes can be proposed as a descriptive theory of quality nursing care within the tension between empirical data and pre-understanding. The theory emphasizes the existential needs such as communicated with, being respected, and being cared for which should be considered important when providing nursing care to patients with cancer.
Keywords: Quality nursing care; Cancer care; Hermeneutic phenomenology; Ricoeur; Attributes of quality; Descriptive theory